Calibration of carbonate-water triple oxygen isotope fractionation: Seeing through diagenesis in ancient carbonates. (1st November 2020) - Wostbrock, Jordan A.G.; Brand, Uwe; Coplen, Tyler B.; Swart, Peter K.; Carlson, Sandra J.; Brearley, Adrian J.; Sharp, Zachary D.
Abstract: High precision triple oxygen isotope measurements of carbonates can better constrain temperatures and oxygen isotope compositions of seawater through geologic time than 18 O/ 16 O measurements alone, but lack of a definitive calibration has hindered progress. In this study, we fluorinated both carbonate and water samples to measure quantitatively the triple oxygen isotope composition of each phase. We compared the oxygen isotope fractionation between carbonate and water for different carbonate materials: calcite synthesized with and without carbonic anhydrase, abiogenic calcite from Devils Hole, and extant biogenic calcite and aragonite of marine origin. We found similar 1000 lnα 18 Occ-wt values for all materials and combined the results with the high temperature experimental data of O'Neil et al. (1969), resulting in the following fractionation equation ( T in Kelvins) 1000 ln α 18 O cc - w t = 2.84 ( ± 0.02 ) × 10 6 T 2 - 2.96 ( ± 0.19 ) . The calcite triple oxygen isotope values yielded a θ - T relationship of θ cc-wt  = –1.39(±0.01)/ T  + 0.5305 whereas the aragonite triple oxygen isotope values yielded a θ - T relationship of θ ara-wt  = –1.53(±0.02)/ T  + 0.5305. The calcite-water triple oxygen isotope equilibrium fractionation equation for natural samples is Δ 17 ′ O cc - Δ 17 ′ O wt = 2.84 ( ± 0.02 ) × 10 6 T 2 - 2.96 ( ± 0.19 ) - 1.39 ( ± 0.01 ) T + 0.5305 - λ . The combined 1000 lnα 18 O and 1000 lnα 17 O relationships can be used to assess equilibrium in ancient samples and to evaluate potential secular changes in the δ 18 O value of seawater. Most of the Phanerozoic samples analyzed in this study, which were determined to be pristine in previous studies, have undergone some level of diagenesis. Two samples appear to preserve their original oxygen isotope compositions and suggest a cool ocean with a δ 18 O value similar to the modern ocean. Using a fluid-rock interaction model, we can "see through" the diagenetic process and estimate the triple oxygen isotope composition of the carbonate prior to alteration. In doing so, we show that for the time intervals and sample locations measured in this study, Phanerozoic oceans had a comparable range of oxygen isotope compositions and temperatures as modern seawater.